AVR ST‐segment changes and prognosis of ST‐segment elevation myocardial infarction. Issue 4 (1st October 2021) - Sedighi, Sogol; Fattahi, Mustafa; Dehghani, Pooyan; Aslani, Amir; Mehdipour Namdar, Zahra; Hassanzadeh, Mani
Abstract: Background: Clinical importance of aVR lead‐related changes in predicting the prognosis of acute myocardial infarction remains uncertain. The present study aimed to assess the value of ST‐segment changes in aVR lead and the outcome and sequels of the first episode of acute ST‐segment elevation myocardial infarction. Methods: This prospective cohort study was conducted on patients suffering first episode of ST‐segment elevation myocardial infarction and underwent percutaneous coronary intervention. Information was collected through hospital‐recorded files reading. The electrocardiogram (ECG) was taken from the patients upon entering the hospital and followed‐up for 30 days to assess cardiovascular complications. Results: In patients with anterior STEMI, with the use of multivariate analysis, admission aVR ST elevation ≥1 mm was found to be a strong and independent predictor of major cardiovascular adverse events (MACE) within 30 days of discharging ( P value for trend .002). In patients with inferior (± RV) ST‐segment elevation myocardial infarction (STEMI), with the use of multivariate analysis, admission aVR ST depression ≥1 mm was found to be a strong and independent predictor of MACE within 30 days of discharging ( P value for trend .01). Conclusion: In patients with anterior STEMI, admission aVR STE ≥1 mm was found to be a strong and independent predictor of MACE within 30 days of discharging. On the other hand, in patients with inferior STEMI, aVR ST depression ≥1 mm was found to be a strong and independent predictor of MACE within 30 days of discharging.